LOW NEUTROPHIL-TO-LMPHOCYTE RATIO DECREASES RISK OF CORONAVIRUS DISEASE IN PREGNANT WOMEN - Anggraini, Nutria Widya Purna; Sulistyowati, Sri (Faculty of Medicine, Trisakti University, 2020)
BACKGROUNDCoronavirus Infection 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is an emergency condition for global public health. Early detection of COVID-19 in pregnant women is needed. The neutrophil-to-lymphocyte ratio (NLR), as a marker of viral inflammatory response, is used to determine the presence of a viral or bacterial infection, both acute and chronic. The objective of this study was to determine the relationship between NLR and the polymerase chain reaction (PCR) swab test results in pregnant women with suspected coronavirus disease 2019.METHODSA cross-sectional study was conducted on 9 pregnant women with suspected COVID-19. The subjects were inpatients at Moewardi Hospital Surakarta from 19 April-19 May 2020, who had rapid tests, complete blood examinations, and PCR swab tests. The NLR was categorized based on early warning scores according to research developed at Zhejiang University, with cut-off point 5.8. Diagnosis of COVID-19 was confirmed by PCR swab tests. Relation between NLR and PCR swab results was analyzed by the prevalence ratio.RESULTSTwo patients (22.2%) had NLR >5.8, with positive swab results in both (100%). Seven patients with NLR <5.8 had positive swabs in only one (33.3%). The relationship between NLR and PCR swab test results showed a prevalence ratio of 0.143 (95% CI 0.023-0.877).CONCLUSIONPregnant women with NLR < 5.8 had a decreased risk of COVID-19. Routine blood examination is more suitable for finding pregnant women with suspected COVID-19.